Antiperovskite materials as promising candidates for efficient tandem photovoltaics: First-principles investigation. (15th August 2022) - Sreedevi, P.D.; Vidya, R.; Ravindran, P.
Abstract: In the past few years, the perovskite tandem solar cells show commendable developments in achieving the power conversion efficiency of 30% which is relatively higher than that produced by the single -junction solar cells. But, to the best of our knowledge, there is no literature available regarding the antiperovskite based tandem solar cells. This is the first study reporting the applicability of some predicted antiperovskite compounds Mg 3 PN, Ca 3 PN, Sr 3 PN, Ba 3 PN, BaSr2 PN, Ba1.5 Sr1.5 PN, and Ba2 SrPN with suitable properties for using as the best absorbing layers in higher efficient tandem solar cell. These seven antiperovskite compounds attain direct band gap nature with band gap values ranging from 1.1 eV to 2.3 eV. The absorption coefficient, optical conductivity and extinction coefficients are found relatively higher in the visible region. Besides, low reflectivity is also analysed in the visible region for the compounds. Low charge carrier effective masses and low recombination rate between the charge carriers can also be observed in the seven materials and thus boost up the carrier mobility and electrical conductivity. Besides, the excitonic binding energy values are also found to be very small for all the predicted compounds. Since all the compounds stabilize in the same crystal structure, the lattice mismatch between each cell will become so less which in turn will be beneficial for making the tandem solar cell. So, it is more suitable to use these materials as the absorbing layers in tandem solar cells apart from use them in single junction photovoltaics since the power conversion efficiency will be more for multijunction/tandem solar cells.